2004
DOI: 10.1111/j.1467-8624.2004.00807.x
|View full text |Cite
|
Sign up to set email alerts
|

Economic Stress, Parenting, and Child Adjustment in Mexican American and European American Families

Abstract: To assess the impact of economic hardship on 111 European American and 167 Mexican American families and their 5th-grade (M age=11.4 years) children, a family stress model was evaluated. Structural equation analyses revealed that economic hardship was linked to indexes of economic pressure that were related to depressive symptoms for mothers and fathers of both ethnicities. Depressive symptoms were linked to marital problems and hostile parenting. Paternal hostile parenting was related to child adjustment prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
350
2
13

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 408 publications
(396 citation statements)
references
References 61 publications
27
350
2
13
Order By: Relevance
“…The latter finding is also consistent with the results from a previous study (Yan, 2005) We also found that there were strong associations between physiques and each socioeconomic factor such as family income, parental occupation and parental education. These findings were consistent with studies that children from high SES family have bigger physiques than those from low SES family (Morton, et al, 2002;McBride, 1990;Mahoney, Kaiser et al, 1999;McLoyd, 1998;Ma, Wu, Yang, 2010;NICHD Early Child Care Research Network, 1998;Ortega, Fang, Perez, et al, 2007;Parke, Coltrane, Duffy, Buriel, Dennis et al, 2004;Rona, Chinn, 1991;Solinger, 1999;Mohanty, Woolhandler, Himmelstein, Pati, Carrasquillo, Bor, 2005;Slesinger, Christenson, Cautley, 1986;Stamatakis, Wardle, Cole, 2010). Finally, by the ANCOVA in which both socioeconomic factors and groups were taken as independent variables and age was taken as a covariate, although strong associations between physiques and group were identified, there were hardly associations between socioeconomic factors and physiques.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The latter finding is also consistent with the results from a previous study (Yan, 2005) We also found that there were strong associations between physiques and each socioeconomic factor such as family income, parental occupation and parental education. These findings were consistent with studies that children from high SES family have bigger physiques than those from low SES family (Morton, et al, 2002;McBride, 1990;Mahoney, Kaiser et al, 1999;McLoyd, 1998;Ma, Wu, Yang, 2010;NICHD Early Child Care Research Network, 1998;Ortega, Fang, Perez, et al, 2007;Parke, Coltrane, Duffy, Buriel, Dennis et al, 2004;Rona, Chinn, 1991;Solinger, 1999;Mohanty, Woolhandler, Himmelstein, Pati, Carrasquillo, Bor, 2005;Slesinger, Christenson, Cautley, 1986;Stamatakis, Wardle, Cole, 2010). Finally, by the ANCOVA in which both socioeconomic factors and groups were taken as independent variables and age was taken as a covariate, although strong associations between physiques and group were identified, there were hardly associations between socioeconomic factors and physiques.…”
Section: Discussionsupporting
confidence: 79%
“…Many studies showed that parental education has a profound influence on child's physical growth. (Parke, Coltrane, Duffy, Buriel, Dennis et al, 2004;Rona & Chinn, 1991;Solinger, 1999). Physiques of children whose parents have high-level education are bigger than those whose parents had low-level education (Mohanty, Woolhandler, Himmelstein, Pati, Carrasquillo, Bor, 2005;Slesinger, Christenson, Cautley, 1986;Stamatakis, Wardle, Cole, 2010;Chin J School Health, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Essa diferença foi mais acentuada na terceira avaliação, quando as crianças cujas famílias possuíam renda até R$100,00, bem abaixo do salário mínimo vigente na época, tiveram uma média do IDM/QI de 83,8; na faixa de renda de R$101,00 a R$310,00, a média eleva-se para 96,6 e na faixa mais alta, Esse resultado é compatível com diversos estudos sobre a relação entre desenvolvimento cognitivo e nível sócio econômico da família ou diferenças de experiências (Eickmann, Lira, & Lima, 2002;Spiess, Büchel & Wagner, 2003), embora essa relação seja mediada por vários fatores. Geralmente, condições de vida associadas à baixa renda, como ambiente pobre e desorganizado, background cultural minoritário, alto estresse dos pais, altas taxas de natalidade, residência em bairros com alta incidência de violência e criminalidade, refletem-se na quantidade e qualidade do envolvimento parental com as crianças e no tipo de experiên-cia proporcionada, afetando o conjunto ou aspectos particulares do desenvolvimento, muitas vezes em interações complexas com variáveis individuais e background étnico e cultural (Dearing, 2004;Parke et al, 2004;Yoshikawa, 1999).…”
Section: Resultsunclassified
“…2 Food insecurity is a type of economic hardship, and the prevalence of food insecurity among households with children is influenced by the household structure and various demographic and disadvantaged socioeconomic factors. [2][3][4][5] Although research suggests that the family environment is negatively influenced in the presence of economic hardship, [6][7][8][9][10][11] few studies have taken an in-depth examination of the family environment by investigating how maternal health problems can influence the food security status of households with young children.…”
Section: Introductionmentioning
confidence: 99%